2022
DOI: 10.26434/chemrxiv-2022-bzzd3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermal imaging and clandestine surveillance using low-cost polymers with long-wave infrared transparency

Abstract: With increasing use of infrared imaging in medical diagnostics, military and civilian surveillance, and navigation of autonomous vehicles, there is a need for low-cost alternatives to traditional materials used in infrared optics such as germanium. Sulfur-rich copolymers hold promise, as they are made from low-cost feedstocks and have a high refractive index. In this report, cyclopentadiene was copolymerized with sulfur to provide a plastic with the highest long-wave infrared transparency reported to date for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…To date, only a few publications have included a Raman study of their inverse vulcanised polymers. 12,[19][20][21] Berk et al, used Raman spectroscopy as a complementary technique to IR spectroscopy, but derived little information from their spectra. 22 Najmah et al, used Raman spectroscopy despite the fluorescence of their polymers to identify the presence of unreacted sulfur, which gave sufficiently strong signals to be seen through the fluorescent background.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few publications have included a Raman study of their inverse vulcanised polymers. 12,[19][20][21] Berk et al, used Raman spectroscopy as a complementary technique to IR spectroscopy, but derived little information from their spectra. 22 Najmah et al, used Raman spectroscopy despite the fluorescence of their polymers to identify the presence of unreacted sulfur, which gave sufficiently strong signals to be seen through the fluorescent background.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that any DCPD formed in the CPD reservoir (left flask, Figure 1E) cannot enter the gas phase and react with the sulfur because the boiling point of DCPD is 170 °C. And while ultrathin sulfur polymer films have recently been made using gaseous monomers, [17] the process in Figure 1E constitutes the first bulk copolymerization of sulfur with a gaseous monomer [18] -a process previously thought to be infeasible. [16] Recently, another method for inverse vulcanization of gaseous monomers was also reported that relies on photochemical activation.…”
Section: Resultsmentioning
confidence: 99%
“…[20] All of these applications, in some way, address issues in sustainability. For example, repairable materials are important for recycling and lifecycle management, [21] sulfur-based thermal imaging replaces low-abundance elements like germanium [18a] and has use in wildlife surveillance and conservation, [22] and pollution control is clearly important for environmental stewardship.…”
Section: Inverse Vulcanizationmentioning
confidence: 99%